Iraq in wartime soldiering, martyrdom, and remembrance - Khoury, Dina Rizk (Cambridge University Press, 2013)
When US-led forces invaded Iraq in 2003, they occupied a country that had been at war for 23 years. Dina Rizk Khoury traces the political, social and cultural processes of the normalization of war in Iraq during the last twenty-three years of Ba'thist rule. Coming on the tenth anniversary of the US-led invasion of Iraq, this book tells a multilayered story of a society in which war has become the norm.